Analisis Auditor Switching dan Faktor-Faktor yang Mempengaruhinya pada Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia - Febri Ariani Lubis; Aria Masdiana Pasaribu; Syamsul Bahri Surbakti (Jurnal EBI, 2021)
This study aims to analyze the effect of Audit Opinion, Management Change, Public Accountant Firm Size, and Client Company Size on Auditor switching in Non-Financial Companies listed on the Indonesia Stock Exchange in 2018-2019. In this study, the population obtained from non-financial companies was 420. The sample obtained for 2 years was 210 samples. The sample data used uses secondary data, namely the annual financial statements of non-financial companies in 2018-2019. The data analysis technique used is logistic regression. The results of this study conclude that the variable of management turnover and the size of KAP have an effect on auditor switching, while audit opinion and the size of the client's company have no effect on auditor switching. Keywords: Audit Opinion, Management Change, Public Accounting Firm Size, Client Firm Size, Auditor Switching